Investigating pre-service teachers’ perceptions on readability tools: a case study in Indonesia - Basori Basori; Diah Wihardini; Imam Rofiki; Elva Riezky Maharany (Institute of Advanced Engineering and Science, 2024)
The readability tools allow us to measure the readability of a text. The previous studies have elaborated the use of readability tools to analyze reading materials, but it is relatively sparse regarding the teaching of readability tools especially involving the second language teaching education (SLTE) program as a context. Therefore, this study aimed to explore the acceptance of pre-service English as a foreign language (EFL) teacher upon readability text tools. It covers their acceptance towards the tools, the extent to how the pre-service teachers accept the Web-FX and Readability Analyzer as readability tools and seeks for participants’ concerns using the tools. The study was conducted at one English Language Education Study Program at in East Java, Indonesia, involving 33 third-year undergraduate students taking pre-teaching program. Having incorporated a qualitative data analysis approach on the students’ text analysis reports and interviews, the study revealed that the participants have positive acceptance of the tools for several reasons. Some final concerns from pre-service teachers after readability tools teachings are presented, including suggestions for future research related to readability tools.